Perancangan Aplikasi Top Up Game Menggunakan Algoritma Collaborative Filtering Berbasis Website - Dery Ramadhan; Kusdarnowo Hantoro; Asep Ramdhani Mahbub (Journal of Informatic and Information Security, 2024)
This research aims to design a game top-up application that utilizes collaborative filtering algorithms as a recommendation method, with a website-based platform. The primary focus is to leverage artificial intelligence to analyze user purchasing patterns and provide personalized and relevant top-up recommendations. The Waterfall development method is employed to ensure that the application development process is structured, from requirement analysis to implementation. Application performance evaluation is conducted to measure the effectiveness of the collaborative filtering algorithm in providing accurate recommendations and enhancing user satisfaction. It is hoped that the results of this research will make a positive contribution to improving game top-up services and strengthening the online gaming experience for users.